2017
DOI: 10.5152/iao.2017.4216
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular Response to Electrical Stimulation of the Otolith Organs. Implications in the Development of A Vestibular Implant for the Improvement of the Sensation of Gravitoinertial Accelerations

Abstract: OBJECTIVE:Electrical stimulation of the utricular and saccular portions of the vestibular nerve improves stability in patients suffering from vestibular dysfunction. The main objective of this study was to evaluate a new technique, vestibular response telemetry (VRT), for measuring the electrically evoked vestibular compound action potential (saccular and utricular) after stimulating the otolith organ (saccular and utricular) in adults. This study used evidence that the otolith organ can be electrically stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Recently, Ramos de Miguel et al (2017) reported initial attempts at utricular stimulation in humans. Three electrodes from a commercial cochlear implant were inserted temporarily in the vestibule near the utricle while attempts were made, with the patient under general anesthesia, to record far-field potentials the authors interpreted as electrically evoked compound action potentials from the electrode array and ocular vestibular evoked myogenic potentials (oVEMPs) for the contralateral eye.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Ramos de Miguel et al (2017) reported initial attempts at utricular stimulation in humans. Three electrodes from a commercial cochlear implant were inserted temporarily in the vestibule near the utricle while attempts were made, with the patient under general anesthesia, to record far-field potentials the authors interpreted as electrically evoked compound action potentials from the electrode array and ocular vestibular evoked myogenic potentials (oVEMPs) for the contralateral eye.…”
Section: Discussionmentioning
confidence: 99%
“…The otoliths can also encode head rotations and contribute to angular VOR compensation ( Sadovnichy et al, 2007 ; Ramos de Miguel et al, 2017 ). However, the topographical organization of otolithic end-organs is complex.…”
Section: Prosthesis Designmentioning
confidence: 99%
“…A device derived from a Nucleus CI24M cochlear implant with bidirectional telemetry and with three active electrodes for vestibular stimulation, were implanted unilaterally in patients selected following Barany criteria for VI, with an absence of vestibular evoked myogenic potentials (VEMPs) and profound deafness ( Ramos de Miguel et al, 2017 ). Subjects were implanted with an extralabyrinthine electrode in the inferior vestibular nerve in a region mainly containing afferent neurons from the saccular macula and likely from the posterior SCC.…”
Section: Human Implantation Studiesmentioning
confidence: 99%
“…This is a (not yet clinically available) strategy to partially restore vestibular function by stimulating the vestibular nerves, using surgically implanted electrodes ( 21–23 ). The electrodes can be implanted inside or close to the semicircular canals ( 24 , 25 ), or inside the otolith organs ( 26 ). Surgically positioning electrodes in a semicircular canal or otolith organ, can destroy the (residual) function of that specific organ.…”
Section: Introductionmentioning
confidence: 99%